Home range of rehabilitated siamang (Symphalangus syndactylus) in fragmented forest areas of South Solok, West Sumatra, Indonesia - RIFTA SEPTIAVI; AADREAN AADREAN; RIZALDI RIZALDI; AURELIEN F. BRULE (Society for Indonesian Biodiversity, 2026)
Abstract. Septiavi R, Aadrean, Rizaldi, Brule AF. 2026. Home range of rehabilitated siamang (Symphalangus syndactylus) in fragmented forest areas of South Solok, West Sumatra, Indonesia. Biodiversitas 27 (1): d270113. https://doi.org/10.13057/biodiv/d270113. Effective post-release adaptation is critical to the long-term success of primate reintroduction programs, yet empirical data on how release duration influences ranging behavior remain limited. This study examined the home range size and spatial use of three rehabilitated siamang (Symphalangus syndactylus) pairs released in fragmented forest areas in the Bukit Tengah Pulau and Bukit Salo forests within the PT KSI concession of South Solok, West Sumatra, Indonesia. The subjects were released at different adaptation durations (9 months, 6 months, and 3 months) before observation. Home range estimates based on the Minimum Convex Polygon (MCP) method showed exploration areas of 26.64 ha, 23.45 ha, and 18.35 ha, respectively. Kernel Density analysis indicated that siamangs with shorter adaptation periods exhibited movements concentrated near feeding sites, whereas those with longer adaptation periods were more dispersed, reflecting greater foraging independence. The Kruskal-Wallis test revealed significant differences in home range size among groups (p<0.05). These findings indicate that longer post-release periods may facilitate greater ranging capacity, an essential factor for territory establishment and survival in the wild. These findings provide evidence-based guidance for optimizing release protocols in future primate conservation programs. Extended monitored release period conditioning combined with post-release habitat restoration is therefore recommended to improve long-term reintroduction success of siamangs and other arboreal primates.